Pulmonary Tuberculosis in Severely-malnourished or HIV-infected Children with Pneumonia: A Review (Journal of Health, Population and Nutrition, 2013)
Presentation of pulmonary tuberculosis (PTB) as acute pneumonia in severely-malnourished and HIVpositive children has received very little attention, although this is very important in the management of pneumonia in children living in communities where TB is highly endemic. Our aim was to identify confirmed TB in children with acute pneumonia and HIV infection and/or severe acute malnutrition (SAM) (weight-for-length/height or weight-for-age z score